(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
The national grid is able to provide round the clock energy supply. Some region of India owing their geographical not able to get continuous power supply from the grid, one such location is Leh. The power delivered in that region is of very low quality, having frequent outage and the reliability of the supply becomes a challenge. During harsh environment the supply and reliability affected greatly due to the restricted movement of man and material. On the other hand, renewable energy supply being located on the site of installation can be able to eliminate such challenges. Hybrid combination of PV and Wind along with some storage facilities can mitigate the challenges. The storage battery increases the project cost and also releases pollutants during their operation. So the study uses the existing national grid to exchange the energy, the combination of PV-wind with the national grid. The study finds out the optimal size of such combination, focusing on the reliability and cost effective energy supply.